Increased suicidality in patients with cluster headache. (September 2019) - Ji Lee, Mi; Cho, Soo-Jin; Wook Park, Jeong; Kyung Chu, Min; Moon, Heui-Soo; Chung, Pil-Wook; Myun Chung, Jae; Sohn, Jong-Hee; Kim, Byung-Kun; Kim, Byung-Su; Kim, Soo-Kyoung; Song, Tae-Jin; et al.
Objective: To investigate suicidality related to cluster headache and factors associated with increased suicidality in cluster headache patients. Methods: In this multicenter study, 193 cluster headache patients were recruited between September 2016 and August 2018. Patients were asked about their suicidality during and between attacks, specifically about passive suicidal ideation, active suicidal ideation, suicide plan, and suicide attempt. Univariable and multivariable logistic regression analyses were performed to evaluate the factors associated with high ictal suicidality (sum of positive response ≥ 2). Patients were followed up when they were in the between-bouts period. Results: A total of 175 cluster headache patients in the in-bout period were included in this study. Passive suicidal ideation, active suicidal ideation, suicidal planning, and suicidal attempt were reported by 111 (64.2%), 62 (35.8%), 10 (5.8%), and four (2.3%) patients during attacks; seven (4.0%), six (3.5%), five (2.9%) and two (1.2%) patients interictally; and none (0%), one (1.9%), one (1.9%), and none (0%) among patients in the between-bouts period. Factors associated with high ictal suicidality were longer disease duration, the Headache Impact Test score, and the Patient Health Question-9 score (multivariable OR = 1.90 per 10-year increase in disease duration, 95% CI = 1.18–3.05, p = 0.008; multivariable OR = 3.19 per 10-point increase in HIT-6, 95% CI = 1.73–5.87, p < 0.001; multivariable OR = 2.11 per 10-point increase in PHQ-9, 95% CI = 1.13–3.95, p = 0.020, respectively). Conclusions: Cluster headache attack carries a high suicidality compared to the interictal or between-bouts state. An intensive treatment to reduce cluster headache burden may be helpful to alleviate suicide risk in cluster headache patients.